The digital era of taxation: Analysing the effectiveness of digital tax adoption on petroleum excise duty revenue - Julius Opiso; Stephen Korutaro Nkundabanyanga; Sulait Tumwine; Twaha Kigongo Kaawaase; Livingstone Senyonga; Simon Echegu (Cogent Business & Management, 2023)
This paper investigates the relationship between digital tax adoption and the performance of petroleum excise duty using a sample of 52 petroleum importing companies in Uganda for the period 2022. Ordered probit regressions were used in the analysis to achieve the study's objectives. Consistent with the results of prior studies, we find a statistically significant and positive association between digital tax adoption and the performance of petroleum excise duty. Distinct from past studies, we further examined the link between the attributes of digital tax adoption and the performance of petroleum excise duty. In line with the technology adoption model, our results revealed that among the digital tax adoption attributes, perceived usefulness, information infrastructure, and digital skills significantly contribute to positive variance in petroleum excise duty performance. Though digital tax adoption has received sizeable study in the literature, its application in the context of petroleum excise duty has received less scholarly attention.
Keywords: 650; digital tax adoption; digital tax adoption attributes; the performance of petroleum excise duty; Uganda